The Effect of Roxadustat on Transfusion-Dependent Myelodysplastic Syndrome Complicated by Chronic Kidney Disease - Ryujiro Hara (Karger Publishers, 2021)
Haematopoietic insufficiency is the treatment target of lower-risk myelodysplastic syndrome (MDS). Although erythropoiesis-stimulating agents (ESAs) are generally effective for treating anaemia, resistance can develop. Hypoxia-inducible factor-prolyl hydroxylase (HIF-PH) improves renal anaemia by promoting endogenous erythropoietin production and normalizing iron metabolism. HIF-PH inhibitors could be used to treat MDS, but their efficacy and safety have not been studied. A 78-year-old female patient with essential thrombocythemia gradually developed anaemia and was diagnosed with therapy-related MDS 4 years later. The anaemia temporarily improved with ESAs, but the patient became transfusion dependent. At the same time, anaemia and chronic renal failure due to nephrosclerosis progressed, and the patient was diagnosed with MDS with renal anaemia. After switching from ESAs to roxadustat, an HIF-PH inhibitor, anaemia improved, and the patient was no longer transfusion dependent. No progression of the underlying disease or any adverse events was observed 4 months after initiating roxadustat.